Reflector heights in the Arctic permafrost areas measured by GNSS interferometric reflectometry - Zhang, Jiahua; Liu, Lin (Zenodo, 2020)
This dataset is about the measurements of reflector height, i.e., the vertical distance between receiver antenna and groud surface, at the GNSS sites in the Arctic permafrost areas. Each data file has four columns. The 1st and 2nd show the time as year and doy, respectively. The 3rd and 4th are the reflector height and its uncertainty, respectively.